Analysis of railway subgrade frost heave deformation based on GPS - Fuxun Ma (Geodesy and Geodynamics, 2016)
In order to analyze the connection between the railway subgrade frost heave deformation and temperature variation, five GPS stations' data were used to monitor the deformation on a certain section of railway subgrade in northeast China. GAMIT software is used to process the data, providing daily solution, daytime solution and nighttime solution. Vertical trends of these five stations were analyzed to investigate frost heave effect on railway subgrade deformation. The results show that the temperature difference between daytime and night induces stations, significant vertical displacement, and the temperature difference between seasons causes settlement of station which appears linear trend.